Wisdom as a devalued value of sustainable development - Łukaszewska, Katarzyna (Studia Ecologiae et Bioethicae, 2019)
In this article, wisdom is presented as an elementary guarantor of development. The value of wisdom is not often treated as a part of development in any of personal, social or economic way. More common is the language of benefits, profits and effects. Wisdom is not treated as very helpful in development because it requires too much time spent thinking. However, as we can learn from Hannah Arendt, there is a connection between evil and the absence of thinking. If sustainable development matters to us, we must remember that wisdom determines our will and choice to do right.